The Important Selection Criteria in Choosing Islamic Banks: A Survey in Bahrain - Al-Hadrami, Abdullah Hamzah; Hidayat, Sutan Emir; Al-Sharbti, Mohamed Isa (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
Selection criteria of banks in general and Islamic banks in particular have been given high attention by the marketing researchers nowadays. But this kind of research is still insufficient in numbers especially in the developing countries. Therefore, this study aims to identify the important selection criteria that are considered by customers in selecting Islamic banks in the Kingdom of Bahrain. A 5-Likert scale survey questionnaire and ANOVA were used as the research method. The results indicate that the religious factors were ranked as the most important selection criteria for selecting Islamic banks. The study also found service quality factors as the second important selection criteria. This study is expected to provide Islamic banks in Bahrain with some inputs in setting up their marketing strategies in order to attract new customers and retain their existing customers. This study is also expected to add value to the literature by providing the updated empirical study in the area. DOI: 10.15408/aiq9i2.4635